Seroprevalence of Leptospira spp infection and its risk factors among domestic dogs in Bogotá, Colombia - Nicolás Céspedes Cárdenas; Gina Polo Infante; Dina Andrea Rangel Pacheco; Juan Pablo Diaz Diaz; Diana Carolina Mejia Wagner; Ricardo Augusto Dias; José Soares Ferreira Neto; Marcos Amaku; Piero Vargas-Pinto; Luis Polo; Jose Henrique Hildebrand Grisi-Filho (Veterinary and Animal Science, 2018)
Different analytical tools were used to determine the seroprevalence of and risk factors associated with Leptospira spp infection in 192 domestic dogs (Canis familiaris) in Bogotá, Colombia. Using the microscopic agglutination test (MAT), a battery of 16 Leptospira serovars were tested. The seroprevalence of Leptospira spp was calculated as 36.46% (95% CI 0.30-0.43). A questionnaire was applied to the dogs’ owners at the time of sampling and the variables “Water sources near home” and “Dog hunting rodents” were identified as risk factors for leptospirosis occurrence in the urban area of Bogotá. Geographical coordinates relating to the dogs’ households were obtained in order to map out the spatial distribution of reactive and unreactive dogs. Additionally, we found that the mean annual precipitation was higher at geographical locations with reactive animals than at those with unreactive dogs (p < 0.05). Preventing exposure of dogs to rodents and waste-water bodies that could be contaminated with Leptospira might effectively reduce occurrences of leptospirosis. Moreover, promoting preventive programs and vaccination of dogs against leptospirosis in areas of higher precipitation and prior to rainy months could be an effective strategy for leptospirosis prevention. Keywords: Leptospirosis, Seroprevalence, Precipitation, Epidemiology, Dogs